Bimbingan Keagamaan dengan Pendekatan Shalawat Sebagai Media Relaksasi di Majelis Taklim Ar-Rahman - Raniasati, Rifani (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
One person who is prone to experiencing stress or mental disorders is the mother. Mothers have an obligation to provide constant and exclusive attention to their children. Due to difficulties in carrying out these tasks, mothers often neglect taking care of their family, children and even themselves. So there is a need for guidance for mothers in dealing with the stress they are experiencing. One of them is to reduce tensions and gain emotional stability. One effort that can be done is with a religiosity relaxation therapy approach using prayer media. Religious guidance is an activity that provides guidance or support to individuals who may experience difficulties in developing their personality optimally to overcome various mental problems. The benefits obtained by someone who carries out prayer activities include a calm heart because they feel close to Allah SWT. and Rasulullah SAW., so that when disaster strikes, he is able to act as an intermediary to achieve dreams, get intercession from the Prophet Muhammad SAW., the congregation will always feel there is a will to improve themselves to be better than before, besides that, the congregation of the taklim assembly will feel that they have found a true purpose in life. guided by the Islamic religion, and also always has positive and good prejudices.